Development of Geometric Transformation E-module Assisted by GeoGebra Software to Enhance Students' Mathematical Abilities during the COVID-19 Pandemic - Faizah, Hanim; Sugandi, Eko; Rofiki, Imam (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
During COVID-19 pandemic, teaching and learning was changed from face-to-face learning to online learning. There were many obstacles in learning mathematics by online-based learning. Such as geometric transformation, some material needs to be represented by a graphic or image, so that students will be easier to learn. This research was aimed to develop geometric transformation e-module assisted by GeoGebra software. The method of this research was used 4D-model developed by Thiagarajan, Semmel, and Semmel. The final draft of the e-module was validated by media and material expert. The final results of this research showed that E-module was valid and feasible to be used in geometric transformation learning process. The feasibility of the module was proven by the average score of the validity test was 88% and 86.67%, that can be converted to very good criteria. Small group trial in using e-module obtained student responses is 82.30% which means that the e-module is good and easy to use. This study has implications in education, that can be used to enrich students' knowledge in the learning process of geometric transformation material, increasing student’s activity, motivation, and learning outcomes.Selama pandemi COVID-19, proses belajar mengajar diubah dari pembelajaran tatap muka menjadi pembelajaran daring. Banyak kendala dalam pembelajaran matematika dengan pembelajaran berbasis online. Seperti transformasi geometri, beberapa materi perlu direpresentasikan dengan grafik atau gambar, agar siswa lebih mudah mempelajarinya. Penelitian ini bertujuan untuk mengembangkan e-modul transformasi geometri berbantuan perangkat lunak GeoGebra. Metode penelitian ini menggunakan model 4D yang dikembangkan oleh Thiagarajan, Semmel, and Semmel. Draf akhir e-modul divalidasi oleh ahli media dan materi. Hasil akhir dari penelitian ini menunjukkan bahwa E-modul sudah valid dan layak digunakan dalam proses pembelajaran transformasi geometri. Kelayakan modul dibuktikan dengan skor rata-rata uji validitas 88% dan 86,67% yang dapat dikonversi menjadi kriteria sangat baik. Uji coba kelompok kecil dalam penggunaan e-modul diperoleh respon siswa sebesar 82,30% yang berarti e-modul sudah baik dan mudah digunakan. Penelitian ini berimplikasi pada pendidikan, yaitu dapat digunakan untuk memperkaya pengetahuan siswa dalam proses pembelajaran materi transformasi geometri, meningkatkan aktivitas, motivasi, dan hasil belajar siswa.